Participation in Crime Prevention according to Buddhist Principles of Local Administrative Organizations in Chaibadan District, Lopburi Province - Sapsombati, Phra Thawatchai; Sawatta , Sutipong; Suraphon , Promgun (Academic MCU Buriram Journal, 2025)
The purposes of this research were: 1) to examine the level of participation in crime prevention by local administrative organizations in Chaibadan District, Lopburi Province, 2) to compare the differences in crime prevention participation based on personal factors of the local population, and 3) to propose a participatory crime prevention model using the Four Right Efforts (Sammappadhāna). The study adopted a mixed-methods approach, integrating quantitative and qualitative research methods. The quantitative research collected data through questionnaires from a sample of 398 respondents, and the data was analyzed using descriptive statistics (frequency, percentage, mean, and standard deviation) and inferential statistics (t-test and F-test). The qualitative research involved in-depth interviews with 12 key informants, and the data was analyzed using descriptive content analysis. The research results found that: 1. Level of Participation: The overall level of participation in crime prevention by local administrative organizations in Chaibadan District was found to be high. When examined by category, the operational participation dimension had the highest mean score of 4.18, followed by benefits utilization (4.18), decision-making (4.11), and evaluation (4.08). 2. Comparison of Participation by Personal Factors: Statistical analysis revealed that individuals with differences in age, education level, occupation, income, and application of the Four Right Efforts had significantly different levels of participation in crime prevention (p < 0.01). However, gender did not significantly influence participation levels. 3. The application of the Four Right Exertions (Sammappadhāna) for mental development and rehabilitation can lead to behavioral change through guidance and awareness in crime prevention, moral and intellectual training, practical implementation, and the effective and just enforcement of laws, in accordance with research principles.